Enlarged perivascular spaces, neuroinflammation and neurological dysfunction in NMOSD patients - Yao, Xiao-Ying; Gao, Mei-Chun; Bai, Shu-Wei; Xie, Li; Song, Ya-Ying; Ding, Jie; Wu, Yi-Fan; Xue, Chun-Ran; Hao, Yong; Zhang, Ying; Guan, Yang-Tai (Frontiers in Immunology, 2022)
Background and Objectives: Cerebrospinal fluid (CSF) and interstitial fluid exchange along a brain-wide network of perivascular spaces (PVS) termed the ‘glymphatic system’. The aquaporin-4 (AQP4) water channels abundantly expressed on astrocytic endfeet play a key role in the CSF circulation in the glymphatic system. Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory demyelinating autoimmune disease of the central nervous system (CNS) featured with a specific autoantibody directed against AQP4 in most of patients. Anti-AQP4 antibodies are likely resulting in the impairment of the brain glymphatic system and the enlargement of PVS in NMOSD patients. In the current study, we aimed to demonstrate the features of EPVS detected by MRI and its association with the CSF anti-AQP4 antibody titer, CNS inflammatory markers, and disease severity in NMOSD patients. Methods: We conducted a retrospective review of a consecutive cohort of 110 patients with NMOSD who had brain MRI. We assessed the correlation of EPVS with markers of neuroinflammation, blood-brain barrier (BBB) function and severity of neurological dysfunction in patients. We used multivariate logistic regression analysis to determine the independent variables associated with disease severity. Results： The median number of total-EPVS was 15.5 (IQR, 11-24.2) in NMOSD patients. The number of total-EPVS was significantly related to EDSS score after correcting for the effects of age and hypertension (r=0.353, p<0.001). The number of total-EPVS was also significantly associated with the titer of CSF anti-AQP4 antibody, the albumin rate (CSF/serum ratios of albumin), the CSF albumin, IgG and IgA levels. Logistic regression analysis showed that total-EPVS and serum albumin level were two independent factors to predict disease severity in NMOSD patients (OR=1.053, p=0.028; OR=0.858, p=0.009 respectively). Furthermore, ROC analysis achieved AUC of 0.736 (0.640-0.831, p<0.001) for total-EPVS to determine severe NMOSD (EDSS 4.5-9.5). Discussion： In our cohort, we found a relationship between EPVS and neuroinflammation and BBB function in NMOSD. Moreover, EPVS might independently predict neurological dysfunction in patients with NMOSD.